1991
DOI: 10.1530/jrf.0.0930043
|View full text |Cite
|
Sign up to set email alerts
|

Evidence to support a follicle-stimulating hormone threshold theory for follicle selection in ewes chronically treated with gonadotrophin-releasing hormone agonist

Abstract: Summary. The mean and peak concentrations of follicle-stimulating hormone (FSH) during the luteal phase of a normal cycle were measured in 8 Welsh Mountain ewes. Gonadotrophin secretion and follicle growth were then suppressed by the chronic administration of the GnRH agonist buserelin for 5 weeks. During the 6th week of agonist treatment, each ewe was given a continuous infusion of FSH to produce a peripheral concentration of FSH equal to either the mean or peak of the gonadotrophin measured for that indivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…There is a great deal of evidence that FSH is the key regulator of recruitment of follicles into waves in most species, and in the ewe, there is a threshold of FSH concentration below which recruitment cannot proceed [15]. This threshold appears to vary among ewes [26] and among follicles within a specific ewe [27]. In the present study (experiment 1), doubling the concentrations of FSH in the peaks that precede follicular waves did not affect either the number or the growth characteristics of small, nonrecruited follicles or FSH-dependent follicles recruited into a wave.…”
Section: Discussionmentioning
confidence: 99%
“…There is a great deal of evidence that FSH is the key regulator of recruitment of follicles into waves in most species, and in the ewe, there is a threshold of FSH concentration below which recruitment cannot proceed [15]. This threshold appears to vary among ewes [26] and among follicles within a specific ewe [27]. In the present study (experiment 1), doubling the concentrations of FSH in the peaks that precede follicular waves did not affect either the number or the growth characteristics of small, nonrecruited follicles or FSH-dependent follicles recruited into a wave.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing FSH levels before luteolysis affects ovulation rate through development of additional estrogenic antral follicles from which preovulatory follicles emerge [6,27,34]. Increasing FSH levels after luteolysis prevents preovulatory follicles from inhibiting further maturation of less-developed follicles through enhanced negative feedback secretion of estradiol and inhibin to suppress FSH release [35,36]. Disabling the latter selection mechanism via administration of FSH during the preovulatory period results in high and variable ovulation rates [2].…”
Section: Discussionmentioning
confidence: 99%
“…Whereas studies in sheep have shown that the growth of follicles to an ovulatory size is dependent on FSH, with the total number of follicles that develop determined by the amount of FSH and the time of exposure [7,8], there are no similar studies in mice. However, in transgenic mice, which lack functional FSH signaling, i.e., the Fshb knockout gene [9], the FSH receptor (Fshr) knockout genes [10,11], or the naturally occurring hypogonadal (hpg) mutant mouse [12] gene, which lacks both LH and FSH, follicles arrest at the preantral stage, confirming that further development is gonadotropin-dependent.…”
Section: Introductionmentioning
confidence: 99%